Application of mathematical modeling in rainfall forecast : a case study of Sungai Sarawak basin - Beatrice Christianus, Bidaun (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Rainfall is a random and probabilistic phenomenon that plays a great role in the life of humans. The study embarks to apply a mathematical modeling in rainfall forecasting for the Sungai Sarawak basin. Recent study reveals that the FS has the ability to simulate long-term rainfa'll up to 300 years is viewed as an important finding in the study of rainfall forecast. Rainfall data was collected from eight rain gauge stations from the Department of Irrigation and Drainage, Sarawak. The data was then analyzed and prepared for missing data, consistency check and adequacy of number of stations. Simple statistical analysis was conducted on the data such as maximum, minimum, mean and standard deviation. 27 years of annual rainfall data were simulated with the Fourier Series equation using spreadsheet. Hence, the result was compared with the Fitting N -term Harmonic Series. The model result reveals that the Fourier Series has the ability to simulate the observed data by being able to describe the rainfall pattern. The result was tested using x2 and RMSE, 2.95 and 1133 mm respectively. There is a reasonable relationship between the simulation and observed data with p-value of 0.93. For future study it is highly recommended to have a refinement in the data analysis that can highly influences the perfonnance of the model.